Simple and Efficient Key Management Method for Hierarchical Wireless Sensor Networks - Altaha, Mohammed A.; Lafta, Wisam Mahmood; Al Ali, Ghazwan Abdulnabi; Alkadhmawee, Ahmed Adil (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2024)
Security is an important consideration for Wireless Sensor Networks (WSNs), and key management plays a pivotal role in facilitating safe communication and data transfer. Key management must be designed with the constraints of these networks in mind, which include limited computation capabilities, memory, and energy. Achieving secure and efficient communication in large-scale WSNs is a significant challenge. In this paper, we propose a simple key management method for securing hierarchical WSNs, which employs only a few hash functions and XOR operations to derive shared keys. Its simplicity makes optimal use of resources and offers an efficient approach to establishing keys for sensor nodes. Simulation results demonstrate that the proposed scheme reduces energy consumption by 15% and decreases the key establishment time by 20% compared to existing methods such as LKMS, while maintaining strong security with low computational and communication costs, which are crucial considerations for WSNs.